Analyzing student assimilation of Japanese phonological transformation rules - Maciejewski, Anthony A., author; Kang, Yun-Sun, author; IEEE, publisher (Colorado State University. Libraries, 1992)
This work describes a method for statistically analyzing a student's proficiency at reading one of the distinct orthographies of Japanese, known as katakana. The result of the analysis is being applied to a Japanese language intelligent tutoring system for appropriately individualizing the student's instruction.
Keywords: natural languages; intelligent tutoring systems; estimation theory; Bayes methods